Three new species of the spider genus Naphrys Edwards (Araneae, Salticidae) under morphology and molecular data with notes in the distribution of Naphrys acerba (Peckham & Peckham) from Mexico - Juan Maldonado-Carrizales; Alejandro Valdez-Mondragón; María L. Jiménez-Jiménez; Javier Ponce-Saavedra (PeerJ)
Herein, we describe three new species of the spider genus Naphrys Edwards, 2003 from Mexico: Naphrys echeri sp. nov., Naphrys tecoxquin sp. nov., and Naphrys tuuca sp. nov. An integrative taxonomic approach was applied, utilizing data from morphology, ultra-morphology, the mitochondrial gene COI, and distribution records. Four molecular methods for species delimitation were implemented under the corrected p-distance Neighbor-Joining (NJ) criteria: (1) Assemble Species by Automatic Partitioning (ASAP); (2) general mixed Yule coalescent (GMYC); (3) Bayesian Poisson tree process (bPTP); and (4) multi-rate Poisson tree process (mPTP). Both morphological and molecular data supported the delimitation and recognition of the three new species. The average interspecific genetic distance (p-distance) within the genus Naphrys is 14%, while the intraspecific genetic distances (p-distance) is <2% for most species. We demonstrate that the natural distribution of Naphrys is not restricted to the Nearctic region. Furthermore, the reported localities herein represent the first with precise locations in the country for Naphrys acerba. In addition, a taxonomic identification key is provided for the species in the genus.